Lymphocyte stimulatory capacities of various Theileria parva isolates: Potential immunogenic and suppressive determinants associated with the parasite antigens and their relevance to vaccines - Ferluga, J.; Eugui, E.M.; O'Brien, C. (International Laboratory for Research on Animal Diseases, 1981)
PAGE 41-42,44 MISSING